Pembuatan dan Pengelolaan Bank Soal Menggunakan ExamView Di SMP Negeri 182 - Indra, Indra; Mufti, Mufti; Wiharto, Yudi; Aryasanti, Agnes; Gata, Grace; Kusdiarto, Djati (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
Today's technology is needed by everyone, even teachers are very dependent on the use of computer applications to support their work. The teacher's job in addition to providing material and explanations, the teacher must also provide questions as an evaluation of student learning after each day after giving an explanation of the material. The purpose of implementing this Community Service is a mandatory activity for lecturers in the Tri Dharma of higher education and the results can help the community. The implementation method is in the form of training and direct practice to the participants. The results of Community Service are in the form of introducing and teaching the use of applications that can help teachers make it easier and faster to make questions in the desired format or form, where the ExamView application is the solution. Easy use and many choices of customizable question formats make this application the choice of educators in making questions faster and can be directly synchronized with the school's Learning Management System. The conclusion of this training was very good, as evidenced by the response of the school and participants, very grateful for the implementation of the training from this community service activity.